Online Review on Hotel Booking Decision: Consumer View - Suwal, Manish; Neupane, Pravin; Pant, Ganesh Datt (International Journal of Atharva, 2025)
Online reviews have become a pivotal factor in shaping consumer decision-making, especially for services like hotel bookings. This study explores how online reviews influence consumer choices, specifically within the context of hotel reservations in Kathmandu, Nepal. A descriptive research design was employed to assess the role of online reviews in hotel booking decisions. Data were gathered through an online survey of 152 participants, using convenience sampling. Respondents represented a range of age groups and demographics, ensuring diversity. The findings revealed a strong tendency for consumers to pay close attention to hotel reviews when making booking decisions. Over 70% of respondents agreed that they always consider reviews, with a notable preference for positive feedback. A significant proportion also acknowledged that a large volume of positive reviews influences their decision, while negative reviews can deter bookings. Interestingly, participants reported mixed responses about the value of excessive positive reviews, with some indicating that an overabundance could make them skeptical. The study underscores the importance of online reviews in consumer decision-making for hotel bookings. Positive reviews play a crucial role in attracting customers, while negative reviews significantly affect booking intentions.